An Analysis of Academic Experience to Develop Entre preneurial Attributes and Motivation among At-Risk Student - Lope Pihie, Zaidatol Akmaliah (The International Journal of Learning, 2007)
Entrepreneurial potential has a lot to do with the spirit and the will within individuals to start a business. Entrepreneurs usually organize and develop their own businesses. Entrepreneurship has no single canonical discipline attached to it, but it benefits from a range of fields, including various knowledge areas, hands on experience, creative visions and insights, network support, and risk taking. Entrepreneurship education for at-risk children can be defined as a method that develops those attitudes that help students at-risk to take responsibility over their own actions, be creative and innovative, and also to develop their creativity in their lives. The development of entrepreneurial talent is important in sustaining a competitive advantage in a global economy that is brought about by innovation. Thus the role of quality entrepreneurship training to identify and nurture entrepreneurial culture among at-risk students is important. A survey was conducted to analyse the academic experience of at-risk students in developing their entrepreneurial attributes and motivation. Data was collected from 14,110 student respondents using questionnaires. The first part of the questionnaire measure student’s entrepreneurial aspiration, which is based on their interest to start a business and be self-employed; entrepreneurial attributes which is measured by self-perception of personal level of entrepreneurship qualities and their entrepreneurial motivation. The second part of questionnaire measure academic experience constructs which comprised of students’ perceptions towards academic self efficacy, computer assisted learning and curriculum experience. The measurement of items in the questionnaire was based on a 5-point Likert scale, with 1 denoting “Strongly disagree”; and 5 denoting “Strongly agree”. SPSS version 12 was used to analyze the data. On the whole, 54% (n=6,918) of the respondents aspired to start up their own business. Sixty nine percent of MARA Training Centre (MTC) students (n=2,721) were interested in setting up their own business, in comparison to 52% (n=1,277) of students enrolled in vocational subjects, and 46% enrolled in Form 4 elective subjects. The results suggest that MTC programs have successfully imparted relatively higher confidence in their students to pursue their own line of entrepreneurial activities. Findings showed that the mean score of the overall entrepreneurial attributes was moderate for all programs with vocational students (mean = 3.51), Form 4 elective (mean = 3.48) and MTC students (mean = 3.59). The students’ score on entrepreneurial motivation was moderately high. It was found that students from MTC had higher attributes than those in the electives and vocational programs in schools. Chi Square analysis was conducted and it suggests that entrepreneurial aspirations of students from different academic programs is significantly different (X²=81.180, df=1, p<.05). The finding showed that academic experience of students significantly predicts their entrepreneurial attributes and motivation of at-risk students.